Cumulative patient effective dose and acute radiation-induced chromosomal DNA damage in children with congenital heart disease. Issue 4 (16th August 2009) - Ait-Ali, Lamia; Andreassi, Maria Grazia; Foffa, Ilenia; Spadoni, Isabella; Vano, Eliseo; Picano, Eugenio
Abstract : Background: The seventh Committee on "Biological Effects of Ionizing Radiation" (BEIR VII, 2006) underlines "the need of studies of infants who are exposed to diagnostic radiation because catheters have been placed in their hearts" . Objective: To determine the lifetime attributable risk (LAR) of cancer associated with the estimated cumulative radiological dose in 59 children (42 male, age 2.8±3.2 years) with complex congenital heart disease, and to assess chromosomal DNA damage after cardiac catheterisation procedures. Methods: In all patients, the cumulative exposure was estimated as effective dose in milliSievert (mSv), and LAR cancer was determined from the BEIR VII report. In a subset of 18 patients (13 male, age 5.2±5.7 years) micronucleus as a biomarker of DNA damage and long-term risk predictor of cancer was assayed before and 2 h after catheterisation procedures. Dose–area product (Gy cm 2 ) was assessed as a measure of patient dose. Results: The median life time cumulative effective dose was 7.7 mSv per patient (range 4.6–41.2). Cardiac catheterisation procedures and CT were responsible for 95% of the total effective dose. For a 1-year-old child, the LAR cancer was 1 in 382 (25th to 75th centiles: 1 in 531 to 1 in 187) and 1 in 156 (25th to 75th centiles: 1 in 239 to 1 in 83) for male and female patients, respectively. Median micronucleus values increased significantly after the procedure in comparison with baseline (before 6‰ vs after 9‰, p=0.02). The median dose–area product value was 20 Gy cm 2 (range 1–277). Conclusion: Children with congenital heart disease are exposed to a significant cumulative dose. Indirect cancer risk estimations and direct DNA data both emphasise the need for strict radiation dose optimisation in children.